2011
DOI: 10.1021/ml100293q
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and SAR of a Series of Agonists at Orphan G Protein-Coupled Receptor 139

Abstract: GPR139 is an orphan G-protein coupled receptor (GPCR) which is primarily expressed in the central nervous system (CNS). In order to explore the biological function of this receptor, selective tool compounds are required. A screening campaign identified compound 1a as a high potency GPR139 agonist with an EC50 = 39 nM in a calcium mobilization assay in CHO-K1 cells stably expressing the GPR139 receptor. In the absence of a known endogenous ligand, the maximum effect was set as 100% for 1a. Screening against 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 7 publications
3
70
0
Order By: Relevance
“…Information on the selectivity and pharmacokinetics of the GPR139 surrogate agonists previously published (TCO-9311 and LP-360924) are limited compared with those of JNJ-63533054. TCO 9311 was found to be a P-glycoprotein substrate with very limited ability to cross the blood-brain barrier (Shi et al, 2011). In contrast, JNJ-63533054 crosses the rat blood-brain barrier after oral administration and achieves exposure in the micromolar range (Dvorak et al, 2015).…”
Section: Gpr139 Is Activated By L-tryptophan and L-phenylalaninementioning
confidence: 99%
See 2 more Smart Citations
“…Information on the selectivity and pharmacokinetics of the GPR139 surrogate agonists previously published (TCO-9311 and LP-360924) are limited compared with those of JNJ-63533054. TCO 9311 was found to be a P-glycoprotein substrate with very limited ability to cross the blood-brain barrier (Shi et al, 2011). In contrast, JNJ-63533054 crosses the rat blood-brain barrier after oral administration and achieves exposure in the micromolar range (Dvorak et al, 2015).…”
Section: Gpr139 Is Activated By L-tryptophan and L-phenylalaninementioning
confidence: 99%
“…In contrast, JNJ-63533054 crosses the rat blood-brain barrier after oral administration and achieves exposure in the micromolar range (Dvorak et al, 2015). Structurally, JNJ-63533054 possesses functional group elements that can be found in the reported hydrazinecarboxamide agonist (TCO-9311) (Shi et al, 2011) having two carbonyls in a 1,4 relationship, separated by two atoms and accompanied by a large flanking hydrophobic surface. It contains fewer hydrogen bond donors and acceptors than does the hydrazinecarboxamide agonist and thus was found to have better physicochemical properties.…”
Section: Gpr139 Is Activated By L-tryptophan and L-phenylalaninementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this reaction could be inhibited by a G q/11 selective inhibitor [2] . This observation was confirmed through the discovery of a series of GPR139 agonists using calcium mobilization assays [7,8] . Susens et al identified the signal transduction pathway using both Ca 2+ mobilization and luciferase-reporter-gene assays.…”
Section: Resultsmentioning
confidence: 77%
“…Shi et al identified compound 1 as a GPR139 receptor agonist with an EC 50 of 39 nmol/L in a calcium mobilization assay for a CHO-K1 cell line stably expressing the human GPR139 for high-throughput screening (HTS) [7] . Isberg et al discovered dipeptides and L-α-amino acids as GPR139 agonists by building a pharmacophore model based on the characterization of 13 compounds reported by Shi et al [8] .…”
Section: Introductionmentioning
confidence: 99%